Estrogen Receptor-Dependent Regulation of Dendritic Cell Development and Function - Laffont, Sophie; Seillet, Cyril; Guéry, Jean-Charles (Frontiers in Immunology, 2017)
Autoimmunity, infectious diseases, and cancer affect women and men differently. Because they tend to develop more vigorous adaptive immune responses than men, women are less susceptible to some infectious diseases but also at higher risk of autoimmunity. The regulation of immune responses by sex-dependent factors probably involves several non-redundant mechanisms. A privileged area of study, however, concerns the role of sex steroid hormones in the biology of innate immune cells, especially dendritic cells (DCs). In recent years, our understanding of the lineage origin of DC populations has expanded, and the lineage-committing transcription factors shaping peripheral DC subsets have been identified. Both progenitor cells and mature DC subsets express estrogen receptors (ER), which are ligand-dependent transcription factors. This suggests that estrogens may contribute to the reported sex differences in immunity by regulating DC biology. Here, we review the recent literature and highlight evidence that estrogen-dependent activation of ERα regulates the development or the functional responses of particular DC subsets. The in vitro model of GM-CSF-induced DC differentiation shows that CD11c+ CD11bint Ly6cneg cells depend on ERα activation by estrogen for their development, and for the acquisition of competence to activate naive CD4+ T lymphocytes and mount a robust pro-inflammatory cytokine response to CD40 stimulation. In this model, estrogen signaling in conjunction with GM-CSF is necessary to promote early Irf-4 expression in macrophage-DC progenitors and their subsequent differentiation into IRF-4hi CD11c+ CD11bint Ly6cneg cells, closely related to the cDC2 subset. The Flt3L-induced model of DC differentiation in turn shows that ERα signaling promotes the development of conventional and plasmacytoid DCs with higher capability of pro-inflammatory cytokine production in response to TLR stimulation. Likewise, cell-intrinsic ER signaling positively regulates the TLR-driven production of type I IFNs in mouse pDCs in vivo. This effect of estrogens likely contributes to the greater proficiency of women’s pDCs than men’s as regards the production of type I IFNs elicited by TLR7 ligands. In summary, evidence is emerging in support of the notion that estrogen signaling regulates important aspects of cDC and pDC development and/or effector functions, in both mice and humans.